Hot Water Extract of Sasa borealis (Hack.) Makino & Shibata Abate Hydrogen Peroxide-Induced Oxidative Stress and Apoptosis in Kidney Epithelial Cells - Ilekuttige Priyan Shanura Fernando; Kirinde Gedara Isuru Sandanuwan Kirindage; Arachchige Maheshika Kumari Jayasinghe; Eui Jeong Han; Mawalle Kankanamge Hasitha Madhawa Dias; Kyung Pil Kang; Sung Ig Moon; Tai Sun Shin; Ayeong Ma; Kyungsook Jung; Ginnae Ahn (MDPI AG, 2022)
Sasa borealis (Hack.) Makino & Shibata or broad-leaf bamboo is famous for its richness of bioactive natural products and its uses in traditional medicine for its anti-inflammatory, diuretic, and antipyretic properties and preventive effects against hypertension, arteriosclerosis, cardiovascular disease, and cancer. The present study investigated the antioxidant activity of S. borealis hot water extract (SBH) and its effects in ameliorating hydrogen peroxide-induced oxidative stress, using an African green monkey kidney epithelial cell line (Vero). Known polyphenols in SBH were quantified by HPLC analysis. SBH indicated a dose-dependent increase for reducing power, ABTS+ (IC50 = 96.44 ± 0.61 µg/mL) and DPPH (IC50 = 125.78 ± 4.41 µg/mL) radical scavenging activities. SBH markedly reduced intracellular reactive oxygen species (ROS) generation in the Vero cells and increased the protective effects against H2O2-induced oxidative stress by reducing apoptosis. Other than the direct involvement in neutralizing ROS, metabolites in SBH were also found to induce NRF2-mediated production of antioxidant enzymes, HO-1, and NQO1. These findings imply that S. borealis hot water extract can be utilized to create nutraceutical and functional foods that can help to relieve the effects of oxidative stress in both acute and chronic kidney injury.